Highly efficient conversion of glycerol and $t$-butanol to biofuel additives over AlPO solid acid catalyst under microwave irradiation technique: kinetic study - Shyam Prasad, K.; Shamshuddin, S. Z. Mohamed (Comptes Rendus. Chimie)
Metal-aluminophosphate solid acids ($m$-AlPO) were prepared and characterized by various techniques such as powder-XRD, FT-IR, BET surface area, SEM, TEM, EDAX, NH$_{3}$-TPD/$n$-butylamine back titration and ICP-OES techniques. These materials were used as catalysts in liquid phase etherification reaction of glycerol with alcohol. In order to obtain good yield of the reaction product, optimization reaction was carried out by varying time, temperature, catalyst weight and molar ratio of reactants. CuAlPO solid acid showed superior performance in a short period of time with 95% glycerol conversion and 68% selectivity to higher ethers (di and tri). The catalytic activity was investigated by three heating techniques (microwave, ultrasonic and conventional). The pre-adsorption experiment obeys the Langmuir–Hinshelwood type mechanism. Kinetic studies were also carried out to determine the activation energy $(E_a)$ and temperature coefficient $(T_c)$ of the catalyst. The catalyst was reused for several reaction cycles without much loss of catalytic activity.